Menggali Potensi TikTok: Pendekatan Pemasaran Digital Produk Kecantikan ‘FAV BEAUTY’ - Hadi Surya, Dalvin; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research analyzes the role of the TikTok social media platform as a means of marketing communication for the